Linguistic Difficulties in Learning Indonesian as a Foreign Language: A Syntactic and Morphological Analysis of Foreign Learners - Roely Ardiansyah; Agung Pranoto; Rini Damayanti (Master Program in Linguistics, Diponegoro University, 2026)
This research looks at the linguistic obstacles encountered by non-native speakers while learning Indonesian, with a focus on syntax and morphology. Despite its wealth of cultural assets, Indonesian students frequently have difficulty with sentence structures that adhere to the Subject-Predicate-Object (SPO) paradigm and with the usage of intricate affixes. Twenty-two foreign students studying Indonesian at the intermediate level participated in this descriptive quantitative research. A questionnaire used to find morphological and syntactic issues provided the data. According to the results, 77.2% of respondents had trouble using prefixes, while 81.8% had trouble comprehending simple sentence patterns. Additionally, learners frequently had trouble telling verbs apart from nouns, which led to numerous mistakes in word usage. These findings imply that there should be more contextual and communicative teaching strategies backed by suitable educational resources and technology.